Model Analisis Sistem Pengolahan Limbah lndustri Tekstil Menggunakan Bioflokulan Moringa Oleifera Lam. - Sukarsono, Sukarsono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
Waste water from textile factories classified into dangerous water as regulated by the Ministry of Environment. This waste water usually flows away into the river environment around of factories. Water treatment unit of textile factory believed as an external unit process which need big budget consequences because it might use imported chemical substances. This situation usually use as a common reasons to pollute the environment. This research is a model solution to reduce a fix budget (cost production) in textile production by using a number of Moringa oleifera as a biofloculant to replace an expensive chemical substances as PAC. This model showed theÂ number of biofloculant at every target number of production and the impact into amount of sludge and water. Linear model commonly found in every stage of simulation. This research showed what kind of preparation needed by environmental factory manager.Â